Colombia : Accounting and Auditing - World Bank (Washington, DC, 2013)
This report is based on the findings of a review of accounting and auditing standards and practices in Colombia. The review exercise focused mainly on the strengths and weaknesses of the institutional framework that supports a corporate financial reporting system in the country. The current legal and regulatory requirements on accounting have led to issuance of conflicting accounting standards from multiple sources. Legal arrangements that gave various regulatory bodies the right to determine the accounting requirements for entities within their jurisdiction have led to the predominance of special-purpose financial reporting. This report provides policy recommendations to improve accounting and auditing practices, including strengthening enforcement mechanisms to ensure compliance with accounting and auditing requirements, and a professional code of ethics for auditors. In this context, it is recommended that a statutory regulatory body be established. Other policy recommendations include the creation of a Higher Council that would be responsible for issuing international accounting and auditing standards as local mandatory requirements for public interest entities; establishing a new professional organization for auditors of financial statements; reforming accounting curriculum and improving significantly the teaching capacity of accounting instructors at universities; and organizing training programs on practical aspects of international auditing standards for accountants, auditors, and others.